2020
DOI: 10.1016/s2215-0366(20)30004-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of self-harm after the diagnosis of psychiatric disorders in Hong Kong, 2000–10: a nested case-control study

Abstract: BackgroundPsychiatric disorders are established risk factors for self-harm. However, variation in risk of self-harm by specific psychiatric disorder, stratified by gender and age, is rarely examined using population representative samples. This study aims to investigate the risk of self-harm following the diagnosis of different psychiatric disorders based on inpatient records retrieved from the Hong Kong Clinical Data Analysis and Reporting System (CDARS). MethodA cohort of 86,353 people with a first-recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 29 publications
3
34
3
Order By: Relevance
“…All CDARS records are anonymised and thus there is no risk of patient identification. Previous studies have validated the coding accuracy of case ascertainment in the CDARS and reported high positive predictive values (PPV) of clinical diagnoses, including hip fractures (100%), gastrointestinal bleeding (100%), atrial fibrillation (95%) and stroke (91%) [15] , [16] , [17] Data from the CDARS have been used in several earlier epidemiological studies and have proved to be reliable [13 , 18] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All CDARS records are anonymised and thus there is no risk of patient identification. Previous studies have validated the coding accuracy of case ascertainment in the CDARS and reported high positive predictive values (PPV) of clinical diagnoses, including hip fractures (100%), gastrointestinal bleeding (100%), atrial fibrillation (95%) and stroke (91%) [15] , [16] , [17] Data from the CDARS have been used in several earlier epidemiological studies and have proved to be reliable [13 , 18] .…”
Section: Methodsmentioning
confidence: 99%
“…This was extracted from either inpatient diagnostic information or from poisoning nature code and traumatic type code in A&E data when applicable. According to previous evidence concerning risk factors for index and repeated self-harm, [3 , 18 , 20] psychiatric disorders and physical illnesses of interest were depression and bipolar disorders (ICD-9-CM code: 296 and 311), alcohol misuse (291 and 303), personality disorders (301), anxiety and neurotic disorders (300, 308, and 309), schizophrenia (295), substance misuse (292, 304, and 305), asthma (493), diabetes (250), migraine (346), epilepsy (345), cancer (140–239), dermatitis and eczema (690–693, and 698), and psoriasis (696).…”
Section: Methodsmentioning
confidence: 99%
“…Data from the CDARS have been used in several earlier epidemiological studies on either the relationship between exposure and health outcomes or disease/medication trends and have proven to be reliable. [40][41][42][43] This case-control study will be nested within the CDARS data from 2001 to 2018.…”
Section: Data Source and Samplementioning
confidence: 99%
“…The risk factors in this study will be divided into two general groups: established risk factors and exploratory risk factors. The established factors include diabetes mellitus (ICD-9-CM 250), 49 midlife hypertension (401), 49 midlife obesity (278), depression (296.2, 296.3, 300.4 and 311), 43 head injuries (800-804, 850-854 and 959.01) 50 and low education. In CDARS, educational level is recorded in five categories: less than primary, primary, secondary, tertiary education or above, and unknown.…”
Section: Established Risk Factorsmentioning
confidence: 99%
“…Nixon et al found that hospitalized adolescents with repetitive SIB experienced urges and tension relieved only by SIB, preoccupation with SIB, and difficulty cutting back on SIB despite negative consequences, which are characteristic of addictions (Nixon, Cloutier, & Aggarwal, 2002). SIB has also been found to co-occur with substance use disorders in hospitalized patients, as well as with behavioral addictions like gambling disorder in community samples (Chai et al, 2020;Farhat et al, 2020). In addition to having potentially addictive features related to repetitive engagement, SIB has been recognized as a way to modify negative emotions, cope with negativity, and provide feelings of excitement and exhilaration (Edmondson, Brennan, & House, 2016).…”
Section: Introductionmentioning
confidence: 99%